Pemanfaatan Kotoran Ternak Sebagai Sumber Energi Alternatif di Kelompok Ternak Sapi Potong Sido Makmur Umbulsari Jember - Nurkholis Nurkholis; Suluh Nusantoro; Aan Awaludin; M. Adhyatma; Bagus Djuni (Indonesian Journal Publisher, 2021)
The sustainability of the livestock business does not only depend on the success of the maintenance system which aims at increasing productivity, but also on the ability to process the resulting livestock waste. Livestock waste is the main source of quality degradation for the environment, this occurs due to the presence of ammonia and methane gas which is formed from the decomposition of organic matter. Ammonia along with other gases can cause acid rain, while methane gas causes a greenhouse effect. This community service partner is a farmer who is part of the